A külföldi tőke és a multinacionális cégek szerepe és a gazdaságra gyakorolt hatása Magyarországon - Tóth-Kmoskó, Éva (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
Presence of the international companies, alien properties, and the foreign capital in Hungary is under a wide social debate. It is the foreign capital which established Hungary’s long-range development and this capital will significantly influence it in the future, too. After the political transformation reintegration into the world economy, establishment of market economy and modernization of the economic structure realized by foreign investments implied an outstanding potential for further development. However, by today the capital drawing ability of Eastern Europe, and Hungary has declined as a result of which adaption to the new situation, reversal of this trend, our ability to keep the capital, and giving the chance to companies in home property all are of stressed importance. I could conclude that it is absolutely necessary to improve the capital attracting ability of Hungary from the aspect of her future developm ent. It is necessary to become specialized in new fields, in activities which need labour force of high qualification, for example we can aim at location of service, financial and adm inistrative centres within the company groups to our country. It is important to increase the efficiency of subventions. Besides, it is advisable to pay attention to regional development if we want prevent companies from leaving our country after that the subventions have been finished. We should pay more attention to the soft factors f capital attraction. It is necessary to consider what qualitative and quantitative conditions a given area has for example, in the fields of life quality, education and culture.